Forest fires in a changing climate and their impacts on air quality - Carvalho, A. (2011)
In a future climate scenario forest fire activity over Portugal will substantially increase and consequently area burned and forest fire emissions to the atmosphere are also expected to increase. This study investigated the impact of future forest fire emissions on air quality over Portugal under the IPCC SRES A2 scenario. Reference and future climate change scenarios were simulated using the MM5/CHIMERE air quality modelling system, which was applied over Europe and over Portugal, using nesting capabilities. The initial and boundary conditions were provided by the HadAM3P model simulations for the reference and the future climate. The forest fire emissions were estimated using a methodology, which included the selection of emission factors for each pollutant, burning efficiency, fuel loads and the predicted area burned. These emissions were added to the simulation grid using specific parameterizations for their vertical distribution. Modelling results for Portugal pointed out that future forest fire activity will increase the O(3) concentrations of almost 23 mu g m(-3) by 2100 but a decrease of approximately 6 mu g m(-3) is detected close to the main forest fire locations. Future forest fire emissions will also impact the PM10 concentrations over Portugal with increases reaching 20 mu g m(-3) along the Northern coastal region in July. The highest increases are estimated over the north and centre of Portugal where the area burned projections in future climate are higher. (C) 2011 Elsevier Ltd. All rights reserved.